C-Myb Dominates TBK1-Mediated Endotoxin Tolerance in Kupffer Cells by Negatively Regulating DTX4. (31st March 2023) - Wu, Yi-Lin; Pan, Le-Han; Yi, Zhu-Jun; Zhang, Wen-Feng; Gong, Jian-Ping
Abstract : As a protective mechanism regulating excessive inflammation, endotoxin tolerance plays a vital role in regulating endotoxin shock. Kupffer cells are players in mediating endotoxin tolerance. Nonetheless, the regulatory mechanism regulating endotoxin tolerance is barely known. A nonclassical IKK kinase called TRAF-associated NF- κ B activator (TANK)-binding kinase 1 (TBK1) can regulate inflammation. Here, we found that TBK1 is required for endotoxin tolerance in Kupffer cells. TBK1 plays a dominant role in regulating endotoxin tolerance by negatively regulating the induction of p100 processing. Deltex E3 ubiquitin ligase 4 (DTX4), a negative regulator of TBK1, can promote TBK1 K48-mediated ubiquitination and indirectly regulate endotoxin tolerance in Kupffer cells. We demonstrate that the c-Myb transcription factor could negatively regulate DTX4. Overexpression of c-Myb can be used to reduce the ubiquitination of TBK1 by reducing DTX4 transcription and to boost the anti-inflammatory effect of endotoxin tolerance. Thus, this study reveals a novel theory of TBK1-mediated endotoxin tolerance in Kupffer cells.